PERAN RUMAH BACA SAMPUN MAOS DALAM MENDUKUNG KEMAMPUAN LITERASI ANAK USIA SEKOLAH DASAR DI KELURAHAN JABUNGAN BANYUMANIK SEMARANG - Febriani, Mawarna; Farizqo Irvan, Moh. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low literacy skills of elementary school-aged children and the suboptimal utilization of the community environment as a space for literacy. Reading houses, as non-formal educational institutions, have strategic potential in supporting the improvement of literacy among elementary school-aged children. This study aims to analyze the role of the Sampun Maos Reading House in supporting the literacy skills of elementary school-aged children in Jabungan Village, Banyumanik, Semarang, as well as to identify the supporting factors and barriers in its implementation. This study employs a qualitative approach using the case study method. The research subjects include reading house managers, children, and parents. Data collection techniques were conducted through data triangulation, namely interviews, observations, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the Sampun Maos Reading House plays a crucial role in enhancing children’s literacy skills both in basic literacy and reading interest through various activities such as read-aloud sessions, reading corners, as well as book-themed play and other creative activities. Supporting factors include parental support, community participation, a conducive environment, and innovative literacy programs. Meanwhile, inhibiting factors include low awareness of literacy among some members of the community, limited parental involvement, and challenges related to digital literacy. Thus, reading houses, as non-formal educational institutions, make a significant contribution to building a community-based culture of literacy among children.